Pengembangan Game 3D Mobile Edukasi untuk Membantu Proses Pembelajaran Pengenalan Benda bagi Anak Tunagrahita - Wenda Novayani; Heni Rachmawati; Qory Yaman (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Children with intellectual disabilities take a long time to understand things and find it difficult to concentrate. Conventional learning at school has not been able to make children with intellectual disabilities focus on education, so learning objectives are not optimal. This research aims to produce educational mobile games in the form of 3D recognition of objects around the school that can help improve the learning process. The research method used is research and development (R&D), where in-game development uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research sample consisted of ten students in grades 5–6 of SD SLB Pelita Hati Pekanbaru. The research instruments are Learning Object Review Instrument (LORI) validation sheets for media and material experts and user satisfaction sheets. Media and material experts validate game feasibility testing and the analysis of the user satisfaction questionnaire. The results showed that object recognition games for children with intellectual disabilities are very valid, motivating, exciting, and increase the concentration of students with intellectual disabilities so as to improve the learning process. Thus, 3D mobile object recognition educational games can be used as an alternative learning medium for children with intellectual disabilities.